Comparison of features of extreme precipitation between stations in inland and coastal Antarctica. (20th September 2022) - Yang, Ran; Yu, Lejiang; Jagovkina, Svetlana; Liang, Kaixin; Yang, Qinghua
Abstract: This study presents different characteristics of precipitation and synoptic‐scale circulation associated with extreme precipitation events in inland and coastal Antarctica. The focus is on two stations, inland Vostok and coastal Casey. We use observed daily precipitation data from years 2004–2017 to investigate and compare the statistics on precipitation at both stations. The key areas for synoptic features favouring extreme precipitation are identified on the basis of air‐mass backward trajectories, computed applying the Lagrangian HYSPLIT model. The air moisture accounting for high‐precipitation events originates from the ocean but in many (some) cases the trajectories cover long distances over the ice sheet before reaching Vostok (Casey). Multiple statistical methods including composite analysis, empirical orthogonal functions (EOF), and self‐organizing maps (SOMs) are used to examine the full view of synoptic patterns. At Vostok in the inland high plateau, ERA‐Interim reanalysis shows that the synoptic patterns governing the extreme precipitation events are relatively complicated. Amplified planetary waves allow water vapour to reach the Vostok Station from different source regions, including the Weddell Sea, Ross Sea, and the Indian Ocean off the Amery Ice Shelf. A dipole structure of negative height anomalies to the west and positive ones to the east of the station is identified as the cause of southward water vapour transport and resulting precipitation at Casey in coastal Antarctica. Abstract : Clusters of 10‐day backward trajectories for (a) 108 extreme precipitation events at Vostok Station and (b) 126 extreme precipitation events at Casey Station. The harsh environment in Antarctica impedes the establishment of the snow ground observation network accompanying the studies on precipitation with in situ data. Distinct characteristics of water vapour transport pathways was found in the inland Vostok and coastal Casey stations. Extreme precipitation at the plateau station is related to amplified planetary waves which allows the oceanic air masses passing through the coastal ice sheets whereas in coastal region is mainly due to the warm and moist air masses brought by the frontal cyclones in the circumpolar trough.